2021
DOI: 10.3390/s21010311
|View full text |Cite
|
Sign up to set email alerts
|

The Role of 8-Amidoquinoline Derivatives as Fluorescent Probes for Zinc Ion Determination

Abstract: Mass-spectrometry-based and X-ray fluorescence-based techniques have allowed the study of the distribution of Zn2+ ions at extracellular and intracellular levels over the past few years. However, there are some issues during purification steps, sample preparation, suitability for quantification, and the instruments’ availability. Therefore, work on fluorescent sensors based on 8-aminoquinoline as tools to detect Zn2+ ions in environmental and biological applications has been popular. Introducing various carbox… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 145 publications
0
12
0
Order By: Relevance
“…As far as we know, quinoline is a compound with low initial fluorescence, but it can form highly fluorescent complexes with metal ions. [30] Therefore, we designed a Schiff base compound (L) bearing a quinoline moiety and imine (Scheme 1), and fluorescence analysis showed that probe L could recognize Zn 2 + with high selectivity and was not affected by other metal ions in CH 3 OH/HEPES solution. In addition, the paper test was successfully carried out to detect zinc ions under 365 nm UV light.…”
Section: Introductionmentioning
confidence: 99%
“…As far as we know, quinoline is a compound with low initial fluorescence, but it can form highly fluorescent complexes with metal ions. [30] Therefore, we designed a Schiff base compound (L) bearing a quinoline moiety and imine (Scheme 1), and fluorescence analysis showed that probe L could recognize Zn 2 + with high selectivity and was not affected by other metal ions in CH 3 OH/HEPES solution. In addition, the paper test was successfully carried out to detect zinc ions under 365 nm UV light.…”
Section: Introductionmentioning
confidence: 99%
“…Colorimetric and uorescent chemosensors based on organic emissive molecules promise innovative solutions for sensor applications, since they are simple to use and can quickly provide chemical information. [15][16][17][18][19][20][21][22][23][24][25][26][27] A plethora of uorescent chemosensors [28][29][30][31][32][33][34][35][36][37] has been developed to date based on different uorophores, such as purine-based Schiff base, 38 rhodamine, 39 aminomethylnaphthol, 40 coumarin, 41 and quinoline containing acetyl hydrazone. 42 One frequent obstacle in searching for Zn 2+ -detection ligands is their apparent inability to distinguish Zn 2+ from its chemically identical neighbour, Cd 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…8-Aminoquinolines have been proven to be potent ionophores, used in many metal-ion chelators, especially for Cu 2+ , Ni 2+ , Zn 2+ and Cd 2+ ions (see examples in Figure 1). [8][9][10][11][12][13] These analytes have gained significant importance recently, owing to their roles in neurobiology, immunology, and even in infectious diseases such as COVID-19. [14][15][16][17][18][19] Figure 1.…”
Section: Introductionmentioning
confidence: 99%